Dukungan Keluarga dan Gangguan Pemenuhan ADL dengan Respon Emosional pada Pasien Pasca Stroke Iskemik - Mahardika, Norma Yulianti; Susilo, Rakhmat; Asiandi, Asiandi; Supriyadi, Supriyadi (Journal of Telenursing (JOTING), 2025)
This study aims to analyze the relationship between family support and impaired fulfillment of ADL with emotional responses in post-ischemic stroke patients at the Neurology Clinic of Prof. Dr. Margono Soekarjo Hospital, Purwokerto. The method used is quantitative with a cross-sectional approach. The results of the study showed that 60 respondents had characteristic results in the gender category, the most in the male gender, as many as 35 respondents (58.3%) and the most age category at the age of >50 years, as many as 47 respondents (78.3%), post-stroke patients suffered the most extended stroke at a time of >6 months as many as 44 respondents (73.3%). The statistical test results showed (p-value 0.001 = <0.05) ischemic. In conclusion, there is a relationship between family support and impaired fulfillment of ADL with emotional responses in post-ischemic stroke patients at the Neurology Clinic of Prof. Dr. Margono Soekarjo Hospital, Purwokerto. Keywords: Family Support, Impaired Fulfillment of ADL, Emotional Response, Ischemic Stroke